Analisis Cerpen Magena Karya Ida Fitri - Wa Ode Irawati (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2022)
This study aims to describe the results of the analysis of the Magena short story from the aspects of syntax, semantics, and pragmatics. The method used in this research is descriptive. The source of data in this research is the short story Magena by Ida Fitri which is analyzed based on syntactic, semantic, and pragmatic aspects. syntactic aspects. The results showed that Magena's short story consisted of 22 main sequences. In the transformation scheme, it is seen that the initial situation occurred at Mike and Magena's marriage. The filter ordeal is seen in the determination of the honeymoon vacation, the main trial is the fall of a flower vase, the triumph/destruction trial is seen in the death of Magena, and the ending situation is seen in Mike's sadness. Semantic aspect analysis shows that Magena's short story consists of 3 characters, namely Magena, Mike, and Aisha. The place where the incident took place was at La Sabira Hill, the Alhambra, and the Palace. The time it happened was when Mike and Magena had their honeymoon vacation. Analysis of the pragmatic aspect: it appears that the speaker/viewer is an outside narrator. The point of view used is the point of view of omniscient (Magenda), all-knowing (Mike and Aisha). The utterances used are direct sentences and narration, precise diction, according to the rules, and commonly used.